An Indicator-based Approach to Measure Urban Sustainability in India - Reddy, B. Sudhakara; Tiwari, Arpit (Journal of Environmental Accounting and Management, 2026)
This study provides a snapshot of the sustainability of selected Indian cities by employing 57 indicators in four dimensions to develop an overall city sustainability index. In recent years, ‘urban sustainability’ has become a prominent concept due to its complexity. Urban areas propel growth and at the same time pose a number of ecological, social and infrastructural problems and risks. High population density and continuous immigration among developing countries produced the highest risk in natural and manmade disasters. These issues and the inability of policy-makers in providing basic services make the cities unsustainable. The objective of the paper is to develop a city sustainability index (CSI) to measure and evaluate the urban regions in terms of sustainable performance. A benchmark approach is used to measure the cumulative performance of the 25 largest Indian cities based on economic, environmental, social and institutional dimensions. The CSI, consisting of four dimensions disaggregates into 14 categories and ultimately into 57 indicators. The data are obtained from public and non-governmental organizations, as also from city officials and experts. The results show that five of India’s largest cities-Delhi, Bangalore, Hyderabad, Chennai and Mumbai-take the lead in sustainability. India’s largest financial center, Mumbai, ranks relatively low in social and environmental dimensions due to inadequate infrastructure, losing out to a new entrant, Hyderabad. Kolkata’s score is harmed by relatively poor infrastructure and low per-capita Gross Domestic Product (GDP). By ranking a sample of diverse cities on a set of specific dimensions the study can serve as a baseline of current conditions and a marker for referencing future results. The benchmarks and indices presented in the study provide a unique resource for the government and the city authorities to learn about the positive and negative attributes of the city and prepare plans for sustainable urban development.